Implementation of the Pancasila Student Profile Strengthening Project in Improving Students' Understanding of Democracy in Junior High School - Nisa Aliza Trigina; Wingkolatin; Nur Fitri Handayani; Novita Majid (Didaktika: Jurnal Kependidikan, 2025)
Education has a strategic role in developing students' potential, both cognitively, skills, and attitudes, one of which is realized through the implementation of the Independent Curriculum with the Pancasila Student Profile Strengthening Project (P5). This study intends to: (1) find out the implementation of P5 in improving students' understanding of democracy at SMP Negeri 11 Samarinda, (2) identify supporting and inhibiting factors for the implementation of P5 related to democracy education, and (3) formulate solutions to overcome obstacles that arise. Qualitative descriptive research is the approach implemented in this study, where data is collected by implementing semi-structured interview techniques, field observation, and documentation. The research informants consisted of PPKn teachers, P5 coaching teachers, and students who were active in project activities. The results of the study show that the implementation of P5 with the theme "Voice of Democracy" with the election of the Student Council President has succeeded in increasing students' understanding of democratic values such as freedom of opinion, social responsibility, and consensus deliberation. Student participation reached 90%, supported by the enthusiasm of students, the active role of teachers, and the support of schools and parents. The obstacles identified include the lack of understanding of some students related to the project objectives and limited implementation time. To overcome these obstacles, schools carry out strategies to strengthen students' understanding from the beginning of the school year, continuous coaching, and improve communication between schools and parents. These findings confirm the importance of P5 as a contextual learning vehicle to foster democratic character in students.